Microbial and clinical factors are related to recurrence of symptoms after childhood lower respiratory tract infection. Issue 2 (28th June 2021) - de Koff, Emma M.; Man, Wing Ho; van Houten, Marlies A.; Vlieger, Arine M.; Chu, Mei Ling J.N.; Sanders, Elisabeth A.M.; Bogaert, Debby
Childhood lower respiratory tract infections (LRTI) are associated with dysbiosis of the nasopharyngeal microbiota, and persistent dysbiosis following the LRTI may in turn be related to recurrent or chronic respiratory problems. Therefore, we aimed to investigate microbial and clinical predictors of early recurrence of respiratory symptoms as well as recovery of the microbial community following hospital admission for LRTI in children. To this end, we collected clinical data and characterised the nasopharyngeal microbiota of 154 children (4 weeks–5 years old) hospitalised for a LRTI (bronchiolitis, pneumonia, wheezing illness or mixed infection) at admission and 4–8 weeks later. Data were compared to 307 age-, sex- and time-matched healthy controls. During follow-up, 66% of cases experienced recurrence of (mild) respiratory symptoms. In cases with recurrence of symptoms during follow-up, we found distinct nasopharyngeal microbiota at hospital admission, with higher levels of Haemophilus influenzae/haemolyticus, Prevotella oris and other gram-negatives and lower levels of Corynebacterium pseudodiphtheriticum/propinquum and Dolosigranulum pigrum compared with healthy controls. Furthermore, in cases with recurrence of respiratory symptoms, recovery of the microbiota was also diminished. Especially in cases with wheezing illness, we observed a high rate of recurrence of respiratory symptoms, as well as diminished microbiota recovery at follow-up. Together, our results suggest a link between the nasopharyngeal microbiota composition during LRTI and early recurrence of respiratory symptoms, as well as diminished microbiota recovery after 4–8 weeks. Future studies should investigate whether (speed of) ecological recovery following childhood LRTI is associated with long-term respiratory problems. Composition of nasopharyngeal microbiota during LRTI in children is related to recurring respiratory symptoms in the following months, and to incomplete microbiota recovery. Future research may pinpoint host and microbial predictors of clinical outcomes. https://bit.ly/3aInAwN